THE DEVELOPMENT OF HAND PUPPET ON STUDENTS’ SPEAKING SKILL THROUGH ROLE PLAYING LEARNING - Siti Marthiasari; Nana Hendracipta; Rina Yuliana (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to develop learning media products for third grade elementary school students at SDN Bugel 3. This research used the Research and Development (R&D) research method with Borg and Gall development procedures. The products produced from this research were hand puppet media. This Hand Puppet was developed into a two-character hand puppet in one puppet or called ‘two in one’ as a visitor. The subjects in this study were 31 students in grade III of SDN Bugel 3. Data collected in this study were through validation of material experts, linguists, media experts and product trial data. From the data obtained, the media of this hand puppet got an average score of expert validation with 91% so that it got "Very Eligible" category, and got an average score of response of 93% included to the criteria of "Very Good". From the results of this study, it can be concluded that the two-character hand puppets developed are feasible and effective in learning and can be used through role playing to foster student speaking skills.